Osteonecrosis of the Femoral Head in an Adolescent on Long-Term Inhalational Corticosteroids - Anthony C. Egger; R. Tracy Ballock (Case Reports in Pediatrics)
A relationship between the development of osteonecrosis of the femoral head and systemic corticosteroids has been well established in the literature, particularly in adults. However, the link between osteonecrosis and inhaled corticosteroids is less researched and understood. We report an usual case report of a 10-year-old male who developed ipsilateral femoral head osteonecrosis after long-term inhalational corticosteroid and intermittent short courses of oral steroid usage with a unique presentation and delayed diagnosis.